2019
DOI: 10.1111/jiec.12852
|View full text |Cite
|
Sign up to set email alerts
|

Closing the loop on platinum from catalytic converters: Contributions from material flow analysis and circularity indicators

Abstract: In this study, material flow analysis (MFA) is applied to quantify and reduce the obstacles for advancing a circular economy (CE) of platinum (Pt) from catalytic converters (CC) in Europe. First, the value chain and related stakeholders are mapped out in an MFA‐like model to both facilitate the assessment of stocks and flows, and get a comprehensive view of potential action levers and resources to close‐the‐loop. Then, through the cross analysis of numerous data sources, two MFA are completed: (i) one general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Circularity of material is an emerging word in recent year, whereas the circular economy is tentatively employed to solve societal and ecological problems ( Anastas, 2020 ). It is defined as a closed loop ( Saidani et al., 2019 ), in particular through waste recycling or circular economy ( Billiet and Trenor, 2020 ; Cobo et al., 2019 ; Tercero Espinoza et al., 2020 ). Anthropogenic circularity science seeks to create a closed-loop material flow typically linking the green chemistry, supply chain, and industrial ecology at different scales ( Cooper et al., 2020 ; Heisel and Rau-Oberhuber, 2020 ; Linder et al., 2017 ).…”
Section: Emergence Of Anthropogenic Circularity Sciencementioning
confidence: 99%
“…Circularity of material is an emerging word in recent year, whereas the circular economy is tentatively employed to solve societal and ecological problems ( Anastas, 2020 ). It is defined as a closed loop ( Saidani et al., 2019 ), in particular through waste recycling or circular economy ( Billiet and Trenor, 2020 ; Cobo et al., 2019 ; Tercero Espinoza et al., 2020 ). Anthropogenic circularity science seeks to create a closed-loop material flow typically linking the green chemistry, supply chain, and industrial ecology at different scales ( Cooper et al., 2020 ; Heisel and Rau-Oberhuber, 2020 ; Linder et al., 2017 ).…”
Section: Emergence Of Anthropogenic Circularity Sciencementioning
confidence: 99%
“…Also, note that few studies published recently provide both illustrative and real-world use cases on how c-indicators have been used to assess, monitor, and improve the circularity performance of products, e.g. : the CPI applied on a catalytic converter used in heavy-duty off-road vehicles and containing a non-negligible amount of precious metals [37], the CEPI and MCI on a tidal energy device [38], or even a prosthetic finger made of polymer materials demonstrating the usefulness of the MDI [33].…”
Section: Illustrative Examples To Design For Circularitymentioning
confidence: 99%
“…whereL j t ð Þ is the platinum loss for process j in year t, N ij t ð Þ is the platinum inflow in process j for catalytic converter in vehicle i in year t, u ij ðtÞ represents the platinum loss rate in process j for catalytic converter in vehicle i in year t. The platinum loss rate is assumed as 10% in the recovery process [14], 1% of collection process [15] and 0.06% as platinum depletion of the EOL catalytic converter [11,16].…”
Section: Simulation Of Historical Stocks and Flowsmentioning
confidence: 99%
“…al. proposed that 65% of platinum loss for catalytic converters in Europe was due to insufficient collections and unregulated exports, while 25% of platinum loss was from in-use dissipation [11]. Saurat et al developed an MFA model of PGMs in Europe to quantify the flows of PGMs in 2004, and the results showed that the automotive industry was the single largest user of primary PGMs, and catalytic converters represented the major PGMs end use [12].…”
Section: Introductionmentioning
confidence: 99%